Hasil Penelitian PENINGKATAN KETERAMPILAN MENULIS CERITA FANTASI MELALUI MODEL PICTURE AND PICTURE PADA SISWA KELAS 7E MTSN 5 KLATEN - Arfina, Hafni; Dwi Bambang Putut Setiyadi; Hersulastuti, Hersulastuti; Purwo Haryono; Nanik Herawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aims to improve the fantasy story writing skills of grade VII E students at MTs Negeri 5 Klaten through the implementation of the Picture and Picture learning model. Fantasy writing skills are essential for students as they develop creative, systematic, and imaginative thinking abilities. However, initial observations showed that students’ writing skills were still low, particularly in developing ideas, organizing story plots, and using appropriate language elements. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 29 students of grade VII E MTs Negeri 5 Klaten. Data were collected through writing tests, observations, and documentation, and analyzed using descriptive quantitative and qualitative techniques. The results showed an improvement in students’ fantasy writing skills from the pre-cycle to Cycle 2. In the pre-cycle, the average score was 69.14 with a mastery level of 34%. In Cycle 1, it increased to 75.17 with 68% mastery. In Cycle 2, it further increased to 80.34 with 86% mastery, exceeding the predetermined success indicator of 80%. The implementation of the Picture and Picture model helped students develop story ideas through visual media, organize plots more coherently, and improve their creativity and participation in learning activities.